A Qualitative Study: Exploring EFL Students' Attitude Towards Learning Writing during Online Learning COVID-19 in Karawang Senior High School - Anasya Azizah; Sidik Indra Nugraha (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
During the Covid-19 outbreak, students are required to carry out the online learning process, this affects their attitude in learning, one of which is writing learning. To content this gap, this study examined about EFL students’ attitude and the elements that influence the attitudes towards learning writing during online learning COVID-19 in Karawang senior high school. This study used qualitative and the data collected through semi-structured interview. Four participants from SMAN 4 Karawang are required to fully participate in the interview. This study revealed that attitudes shown by EFL students towards learning writing during online learning COVID-19 are positive attitudes. The students showed interest in learning writing during online learning although the students more prefer to learn writing in face-to-face learning. This study also revealed that there were some factors that influences students’ attitude towards learning writing during online learning COVID-19.